Juvenile hormone enhances viral activity in bumble bees - Assaf Tzdaka; Elad Bonda; Adam G. Dolezal; Nor Chejanovsky; Hagai Y. Shpigler (Journal of Invertebrate Pathology, 2026)

Ontogeny of immunity and natural viral infection in Apis mellifera drones and workers - Tal Erez; Angelina Fathia Osabutey; Sharif Hamdo; Elad Bonda; Assaf Otmy; Nor Chejanovsky; Victoria Soroker (Journal of Invertebrate Pathology, 2024)

Nosema ceranae in Apis mellifera : a 12 years postdetection perspective - Raquel Martín‐Hernández; Carolina Bartolomé; Nor Chejanovsky; Yves Le Conte; Anne Dalmon; Claudia Dussaubat; Pilar García‐Palencia; Aranzazu Meana; M. Alice Pinto; Victoria Soroker; Mariano Higes (Environmental Microbiology, 2018)
Summary Nosema ceranae is a hot topic in honey bee health as reflected by numerous papers published every year. This review presents an update of the knowledge generated in the last 12 years in the field of N. ceranae research, addressing the routes of transmission, population structure and genetic diversity. This includes description of how the infection modifies the honey bee's metabolism, the immune response and other vital functions. The effects on individual honey bees will have a direct impact on the colony by leading to losses in the adult's population. The absence of clear clinical signs could keep the infection unnoticed by the beekeeper for long periods. The influence of the environmental conditions, beekeeping practices, bee genetics and the interaction with pesticides and other pathogens will have a direct influence on the prognosis of the disease. This review is approached from the point of view of the Mediterranean countries where the professional beekeeping has a high representation and where this pathogen is reported as an important threat.

Identification and Classification of the Spodoptera littoralis Nucleopolyhedrovirus Inhibitor of Apoptosis Gene - Qingzhen Liu; Yipeng Qi; Nor Chejanovsky (Virus Genes, 2003)

Book Review - Nor Chejanovsky (Virus Genes, 1999)

Isolation, Replication and Polyhedrin Gene Sequence of an Israeli Helicoverpa Armigera Single Nucleopolyhedrovirus - Hadassah Rivkin; Michael Mor; Nor Chejanovsky (Virus Genes, 1998)